Relações de gênero no serviço social: a predominância de mulheres no curso de serviço social do ICSEZ- UFAM - Souza, Bárbara Idalina Coelho de (Brasil, 2024)
This Course Completion Work proposed a socio-historical conception of Social Work, highlighting the emergence in Brazil in the 1930s and 1960s, focusing on the professionalization of Social Work. Discussing the influence of gender relations in the profession, highlighting the struggle for the emancipation of women in Brazilian society and the relations between gender and social work. This work was motivated by observing why the course is mostly made up of women and there are few male professionals in the Social Service course at the Institute of Social Sciences, Education and Animal Science (ICSEZ- UFAM) in the city of Parintins- AM and discussing reasons why brings from this reality. In view of this, the general objective of this work is to analyze the elements that determine the prevalence of women in training in social work, with the following specific objectives: pointing out socio-historical influences for professional training; highlight the historical aspects of feminization in the relationship between Gender and Social Work; the predominance of women in the profession in the Social Service course at the ICSEZ-UFAM campus, which is consolidated in the Municipality of Parintins-Am. To this end, the study investigated understanding this relationship between gender and the profession, highlighting why women prevail in the Social Service course at ICSEZ-UFAM, using historical-dialectic materialism and data analysis that sought to extract relevant information from institutional documents for the understanding the relationship between gender and profession in the field of Social Work. In view of this, the results obtained provide an explanatory overview of the trajectory of Social Work and the predominance of women in the profession and in the Social Service course at ICSEZ-UFAM, as well as opening space for reflections on inclusion, gender diversity and future challenges of the profession. KEYWORD: Social Service; Gender; Feminization; ICSEZ- UFAM.